Investigating Influenza Virus Polymerase Activity in Feline Cells Based on the Influenza Virus Minigenome Replication System Driven by the Feline RNA Polymerase I Promoter - Lu, Gang; Zheng, Feiyan; Ou, Jiajun; Yin, Xin; Li, Shoujun (Frontiers in Immunology, 2022)
Emerging influenza virus poses a health threat to humans and animals. Domestic cats have recently been identified as a potential source of zoonotic influenza virus. The influenza virus minigenome replication system based on the RNA polymerase I (PolI) promoter is the most widely used tool for investigating polymerase activity. It could help determine host factors or viral proteins influencing influenza virus polymerase activity in vitro. However, influenza virus polymerase activity has never been studied in feline cells thus far. In the present study, the feline RNA PolI promoter was identified in the intergenic spacer regions between adjacent upstream 28S and downstream 18S rRNA genes in the cat (Felis catus) genome using bioinformatics strategies. The transcription initiation site of the feline RNA PolI promoter was predicted. The feline RNA PolI promoter was cloned from CRFK cells, and a promoter size of 250 bp contained a sequence with sufficient PolI promoter activity by a dual-luciferase reporter assay. The influenza virus minigenome replication system based on the feline RNA PolI promoter was then established. Using this system, the feline RNA PolI promoter was determined to have significantly higher transcriptional activity than the human and chicken RNA PolI promoters in feline cells, and equine (H3N8) influenza virus presented higher polymerase activity than human (H1N1) and canine (H3N2) influenza viruses. In addition, feline myxovirus resistance protein 1 (Mx1) and baloxavir were observed to inhibit influenza virus polymerase activity in vitro in a dose-dependent manner. Our study will help further investigations on the molecular mechanism of host adaptation and cross-species transmission of influenza virus in cats.